2014
DOI: 10.1016/j.resuscitation.2014.01.028
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and pooled analysis of CPR-associated cardiovascular and thoracic injuries

Abstract: OBJECTIVE The incidence of thoracic injuries resulting from cardiopulmonary resuscitation (CPR) is not well characterized. We describe a case in which a CPR-associated atrial rupture was identified with ultrasound and successfully managed in the intensive care unit with a bedside thoracotomy and atrial repair. We then describe a systematic review with pooled data analysis of CPR-associated cardiovascular, pulmonary, pleural, and thoracic wall injuries. DATA SOURCES PubMed, Scopus, EMBASE, and Web of Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
122
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 81 publications
(114 reference statements)
9
122
0
3
Order By: Relevance
“…Miller et al 5 compared standard CPR methodology (chest compressions using the hands only) with CPR, using active compression devices (ACDs) employing either suction cup, automated piston, or load-distributing band technologies. Their findings showed that sternal and rib fracture rates, respectively, were 8.5% and 25.9% in manual compression, 80.6% and 47.2% for suction cup ACD, and 16.9% and 25.4% for piston ACD.…”
Section: Cjem Jcmumentioning
confidence: 99%
See 1 more Smart Citation
“…Miller et al 5 compared standard CPR methodology (chest compressions using the hands only) with CPR, using active compression devices (ACDs) employing either suction cup, automated piston, or load-distributing band technologies. Their findings showed that sternal and rib fracture rates, respectively, were 8.5% and 25.9% in manual compression, 80.6% and 47.2% for suction cup ACD, and 16.9% and 25.4% for piston ACD.…”
Section: Cjem Jcmumentioning
confidence: 99%
“…Similarly, in a review of 2659 autopsy cases, only three incidences of right ventricular rupture secondary to CPR were identified. 6 Last, two comprehensive meta-analyses of CPRassociated injuries found myocardial rupture in only 5 of 818 (0.6%) 5 and <1% of cases. Resuscitation-associated myocardial injury has been observed in a number of clinical settings, including cases of acute myocardial infarction, 8 broken ribs, 6,9 multiple large pulmonary emboli, 10 and recent lung and pericardial surgery.…”
Section: Cjem Jcmumentioning
confidence: 99%
“…In addition, even brief external compressions can pose significant risks of cardiac damage shortly after heart surgery, as noted in multiple case reports of massive hemorrhage subsequent to CPR in these patients. 7,8 A recent meta-analysis 9 in noncardiac surgery patients receiving ECC identified a high rate of complications, including pericardial injury (8.9%), fractured sternum (15%), and rib fractures (32%), as well as additional Given the potential for harm from even brief compressions, it is reasonable to defer ECC momentarily for more definitive therapies, as long as they are timely:…”
Section: Cardiopulmonary Resuscitationmentioning
confidence: 99%
“…The most common CPR related injuries are located on the thorax and affect especially the skeleton: rib fractures, fractures of the sternum (3,7) and flail chest (7). Nevertheless, in children, whose thoracic cage is still quite elastic, bone injuries are rarely reported -0-2% [9].…”
Section: öZetmentioning
confidence: 99%